Optic Nerve 2019
DOI: 10.5772/intechopen.79827
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the Human Optic Nerve: Structure and Function

Abstract: The optic nerve (ON) is constituted by the axons of the retinal ganglion cells (RGCs). These axons are distributed in an organized pattern from the soma of the RGC to the lateral geniculated nucleus (where most of the neurons synapse). The key points of the ON are the optic nerve head and chiasm. This chapter will include a detailed and updated review of the ON different parts: RGC axons, glial cells, connective tissue of the lamina cribrosa and the septum and the blood vessels derivate from the central retina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 152 publications
1
39
0
2
Order By: Relevance
“…The optic nerve is customarily separated into four main regions. These are well described in reference [16] Fig. 1 in Chapter 2 page 13 and in reference [17] Fig.…”
Section: Introductionsupporting
confidence: 58%
“…The optic nerve is customarily separated into four main regions. These are well described in reference [16] Fig. 1 in Chapter 2 page 13 and in reference [17] Fig.…”
Section: Introductionsupporting
confidence: 58%
“…The retinogeniculate pathway (RGVP) begins at the retina, passes through the optic nerve, the optic chiasm, and the optic tract, and finally connects to the lateral geniculate nucleus (LGN; Salazar et al, 2019 ; Purves et al, 2001 ). See Figure 1 for an anatomical overview.…”
Section: Introductionmentioning
confidence: 99%
“…The GCC may be superior to the circumpapillary RNFL since there is an enrichment of RGCs combined with retinotopic segregation. 62 Ganglion cell complex analysis has been compared to RNFL analysis using the special domain ocular coherence tomographer (SD-OCT), and it has been found that the two areas on the fundus have comparable diagnostic accuracy for glaucoma. 63 In a study by Kim et al, 64 it was found that macular GCC thickness was comparable to RNFL thickness in early, moderate and severe glaucoma.…”
Section: The Utility Of Gcc and Rnfl Evaluation In Glaucomamentioning
confidence: 99%